Asymptomatic nasopharyngeal carriage of multidrug resistant bacteria among children at University of Gondar Hospital Northwest Ethiopia Revealing Hidden Health Risks - Abebe Birhanu; Azanaw Amare; Mitkie Tigabie; Getachew Bitew; Tena Cherkos; Eden Getaneh; Feleke Moges (Scientific Reports)
Abstract Gram-negative bacteria in the nasopharynx can eventually invade bacteria-limited sites and cause serious illnesses such as meningitis, otitis media, and pneumonia. However, data related to the carriage of these bacteria in children attending outpatient departments in the study area are limited. To assess nasopharyngeal carriage, antibiotic susceptibility patterns, and associated factors of gram-negative bacteria among children attending the outpatient department at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. A hospital-based cross-sectional study was conducted from September 1, 2023, to December 30, 2023. A total of 385 children aged 3 to 14 years were enrolled using a systematic random sampling technique. Sociodemographic and clinical data were collected using a semistructured questionnaire. A total of 385 nasopharyngeal samples were collected using a sterile specimen collection nasopharyngeal swab, transported using Amie’s transport medium, and subsequently inoculated on chocolate agar, blood agar, modified thayer martin agar, and MacConkey agar plates. Bacterial species were identified by colony morphology, Gram staining, and biochemical tests such as oxidase tests, satellitism tests, and carbohydrate utilization tests. An antibiotic susceptibility test was performed using the Kirby–Bauer and modified Kirby–Bauer methods on Mueller–Hinton agar plates. The data were entered into Epi-Data version 4.6.0.6 and exported to SPSS version 25 for analysis. The adjusted odds ratio at a 95% confidence interval with a P value of < 0.05 in the binary logistic regression model was considered to indicate statistical significance. The overall nasopharyngeal carriage of gram-negative bacteria was 146 (37.9%) (95% CI: 33.2–42.9). Among these, nonfastidious gram-negative bacteria represented 45 (11.7%), followed by M. catarrhalis 41 (10.6%), N. meningitidis 34 (8.8%), and H. influenzae 26 (6.8%). The isolates exhibited high resistance to tetracycline (85; 75.9%), trimethoprim-sulfamethoxazole (105; 71.9%), ampicillin (76; 67.9%), and amoxicillin/clavulanic acid (60; 69.8%) but high susceptibility to meropenem (122; 83.6%), gentamicin (73; 84.9%), and minocycline (87; 72.5%). There were 99 total multidrug-resistant strains (67.8%, 95% CI: 59.7–75.0). Male sex (AOR = 1.785, 95% CI: 1.102–2.892, P = 0.019), smoking (AOR = 2.675, 95% CI: 1.149–6.230, P = 0.022), and large family size (≥ 5) (AOR = 1.857, 95% CI: 1.140–3.023, P = 0.013) were risk factors for nasopharyngeal colonization. Increased nasopharyngeal colonization of multidrug-resistant gram-negative isolates was observed in this study. Gentamicin, minocycline, and meropenem were the most effective antibiotics for the tested isolates. Bacterial colonization increased with increasing family size, smoking status, and male sex. Therefore, a definitive diagnosis in the outpatient pediatric department should be based on culture and susceptibility test results.